Assessing Workplace Bullying and Its Outcomes: The Paradoxical Role of Perceived Power Imbalance Between Target and Perpetrator - Nielsen, Morten Birkeland; Finne, Live Bakke; Parveen, Sana; Einarsen, Ståle Valvatne (Frontiers in Psychology, 2022)
This study investigates the role of perceived power relation between target and perpetrator regarding victimization and turnover intent following exposure to bullying behavior at the workplace. We hypothesized that 1) targets of bullying behavior who self-label as victims experience a larger power imbalance with the perpetrator compared to targets who do not self-label as victims, and 2) that the association between exposure to bullying behavior and intent to leave the job is stronger when there is power balance between target and perpetrator than when there is a power imbalance. The hypotheses were tested in a probability sample of employees working in the child welfare service in Oslo municipality, Norway, and that had been exposed to at least one instance of mistreatment from a colleague at their workplace (N=374). Targets of bullying behavior who self-labeled as victims reported a larger power imbalance with the perpetrator. Supporting the study hypothesis, and representing a reverse buffering effect, exposure to bullying behavior was most strongly associated with intent to leave among targets in power balance with the perpetrator. For targets in a perceived power imbalance, both low and high exposure to bullying behavior were associated with higher levels of intent to leave. These findings highlight the importance of implementing measures directed at preventing bullying and other forms of mistreatment, irrespective of the power relation between the two parties.